Kierkegaard, Communication, and Virtue : Authorship as Edification - Tietjen, Mark A. (Book collections on Project MUSE., 2013)
In contrast to some postmodern and deconstructionist readings, the author believes that the purpose behind Kierkegaard's writings is the moral and religious improvement of the reader. The author defends Kierkegaard against claims that certain features of his works, such as pseudonymity, indirect communication, irony, and satire are self-deceived or deceitful. This book reveals how they are directly related to the virtues or moral issues being discussed. In fact, the author argues, the manner of presentation is a critical element of the philosophical message being conveyed. Reading broadly in Kierkegaard's writings, he develops a hermeneutics of trust that illustrates Kierkegaard's aim to evoke faith in his reader.